Thiopental Elevates Steady-State Levels of Intracellular Ca2+ and Zn2+ in Rat Thymic Lymphocytes: Toxicity test of thiopental on rat thymic lymphocytes - Norio Kamemura; Keisuke Oyama; Shinya Ueno; Mizuki Mizobuchi; Kazumi Ishidoh; Naoki Kanematsu (Journal of Tropical Pharmacy and Chemistry, 2020)
Thiopental is an ultra-short-acting barbiturate and has been used commonly in the induction phase of general anesthesia. However, the toxic effect of thiopental is not completely clear.?The effect of thiopental on intracellular Ca2+ ([Ca2+]i) levels was investigated in non-excitable cells. Experiments were carried out using a flow-cytometric technique, rat thymic lymphocytes (as non-excitable cells), and appropriate fluorescent probes. Treatment of cells with 300 µM thiopental increased Fluo-3 fluorescence intensity, indicating elevation of [Ca2+]i. This increase was partially attenuated by a chelator of intracellular Zn2+. Thus, thiopental elevated both [Ca2+]i and intracellular Zn2+ ([Zn2+]i) levels. Under intracellular Zn2+-free conditions, 100–300 µM thiopental was still able to induce a statistically significant increase in [Ca2+]i, whereas removal of extracellular Ca2+ greatly reduced the increase in [Ca2+]i induced by this dose of thiopental. Therefore, the thiopental-induced increase in [Ca2+]i was mainly due to an increased influx of Ca2+. Treatment of cells with 300 µM thiopental increased FluoZin-3 fluorescence intensity, indicating the presence of [Zn2+]i, both in the presence and absence of extracellular Zn2+. The thiopental-induced elevation of [Zn2+]i was due to an increase in both influx of Zn2+ and intracellular Zn2+ release. Concanavalin A (10 µg/mL) augmented Fluo-3 fluorescence in the presence of an intracellular Zn2+ chelator. The combination of concanavalin A and 100–300 µM thiopental synergistically increased [Ca2+]i. Results suggest that thiopental increases [Ca2+]i in both quiescent and activated lymphocytes, possibly resulting in modulation of immune system function.